Research on vibration isolation and noise reduction technology for the metro depot. Issue 1 (1st February 2022) - Peng, Guangzhao; Fu, Kun; Li, Zhuang; Ba, Jian; Huang, Zhibin; Zeng, Zhiping; Yin, Huatuo; Tang, Qihui
Abstract: Under the situation of increasingly tight land resources, the development of depot superstructures has been applied in many cities.The noise generated by the passage of subway vehicles and the vibration of buildings are problems that need to be solved urgently. The use of vibration and noise reduction measures for the track is an important solution.In order to study the vibration reduction effect of the depot vibration reduction measures, taking the Guangzhou Metro Chentougang Depot as an example, the vibration and noise reduction technology of the depot is studied.The research results show that: (1) It can be seen from Table 1 and Table 2 that after the vehicle speed is corrected to the same speed, the Z vibration level of the trapezoidal sleeper section at the foot of the ballast slope is lower than that of the ordinary transverse sleeper section, and the train speed is 10km/h (low speed). The insertion loss VLZ is 8.24dB, and the insertion loss VLZ is 8.53dB under the train speed of 35km/h (high speed).(2) At the measuring point 7.5m away from the centerline of the track, the Z vibration level of the trapezoidal sleeper section is smaller than that of the ordinary transverse sleeper. The insertion loss VLZ under low-speed conditions is 8.60dB, and the insertion loss VLZ under high-speed conditions is 8.93dB.